Psychological Suffering, Medicalization and Women: Contributions in the Field of Public Health - Medeiros, Luciana Fernandes de; Araújo, Gisely da Costa; Costa, Loyanne Monyk Torres; Oliveira, Isabelly Cristina Soares de; Veras, Renata Meira (Estudos e Pesquisas em Psicologia, 2021)
In recent years we have seen a growing psychological suffering in women attended in primary health care in developing countries. This paper aims to analyze psychological suffering in a small city in northeastern Brazil and its relationship with medicalization. We applied 202 SRQ-20 questionnaires in 3 Basic Health Units in the first research step, which were analyzed with statistical support. In the second step, four women were interviewed in the primary health care service and the data were analyzed from Institutional Ethnography perspective. The results demonstrated a high number of primary health care users in psychological suffering (47.02%). The data also points to a significant prevalence of women in psychological suffering, the use of medicines and the struggles in dealing with the difficulties of everyday life. The medicalization of psychological suffering appeared several times in this study through the invisibility of these sufferings under the blanket of biomedical and medicalizing discourse. Those facts can affect contemporary women and the contradictions of being a woman in a capitalist and patriarchal society.